Taro (colocacia esculenta) as a protein source for growing pigs fed a basal diet of rice bran : - Manivanh, Nouphone (Can Tho university, 2012)
The objectives of the thesis were to study the use of ansiled taro foliage (leaves + stema) as the main source of protein for growing pigs fed rice bran as the basal diet